Formação Docente E Tecnologias Digitais: Estudo De Caso Da Pedagogia Da Unifesp Sob Enfoque Dialógico - Vieira, Paulo Luiz [UNIFESP] (2017)
The present research aims to understand the ways in which the legal recommendations regarding to integration of digital information and communication technologies (DTIC) in courses carried out by the professors of the Pedagogy course in Unifesp, by thematizing them in their disciplines. This work is integrates the research, entitled "Initial teacher training in the first years of elementary school to integrate digital information and communication technologies into teaching and learning processes: an instrumental case study in Pedagogy courses at three federal public universities", coordinated by Prof. Lucila Pesce and developed with the support of CNPq. This research has as corpus the undergraduate course in Pedagogy of Unifesp and it is based on the premises of qualitative research, characterized as an educational case study. The theoretical framework of this study is based on the sociohistorical approach, with the premises of Dialogia (BAKHTIN, 1987) and mediation (VYGOSTSKY, 1984). It also includes the studies related to the TDIC in the field of education with concepts as instructionalism and constructivism (VALENTE, 2002), digital pedagogical interaction (SILVA, 2002), culturalism (BONILLA, 2010), digital dialogue (PESCE, 2007, 2010, 2013), shared mediation (BRUNO, 2012) and the social use of the DTIC (PRETTO, 2015). In the field of language this research counts on the studies on literacy (SOARES, 2002) and multiliteracies (ROJO, 2014). Dealing with the hypothesis that the pedagogic course of Unifesp contemplates partially the pedagogical use of the DTIC in its formative structure, we selected 7 (seven) disciplines that thematizes the DTIC in its curricular structure and 8 (eight) teachers responsible for such disciplines. In the development of the research, we developed the documentary analysis of the Pedagogy course (pedagogical project and the disciplines’ programs) and the thematic analysis of content, with the statements of the selected teachers (semistructured interview). In the data analysis we used three initial categories extracted from the UNESCO TSC-ICT document (2008): a) Literacy in technology; B) Deepening of knowledge, c) Creation of knowledge. We also obtained a fourth emergent category of teachers' statements: d) Challenges in the use of DTIC. The discussion of the results suggests that the re-signification carried out by the teachers we interviewed in the course of Unifesp Pedagogy is closer to the category of analysis “Knowledge deepening”, with the reflexive use of the DTIC in pedagogical practices and that there is a preliminary development of the culturalist use of DTIC in the pedagogical practices analyzed. The research suggests that the educational praxis in relation to the pedagogical use of the DTIC is not restricted to the teaching didactic technical competences, but it larges into the field of the educational political role.